Tensile properties of epoxy grout incorporating graphene nanoplatelets for pipeline repair - Zainal, Nurfarahin; Arifin, Hanis Hazirah; Zardasti, Libriati; Yahaya, Nordin; Lim, Kar Sing; Lai, Jian Wey; Md Noor, Norhazilan (EDP Sciences, 2018)
In oil and gas industry, fibre-reinforced polymer (FRP) composite are widely used to repair pipeline subjected to external metal loss. This repair technique can be done by incorporating epoxy grout as infill material to smoothen the defect on pipeline surface and later wrapped with a composite wrap to restore the strength of the pipe. This paper attempts to investigate the behaviour of an epoxy grout with 0.5wt% graphene nanoplatelets (GnPs) under tensile loading according to the ASTM D638. GnPs were dispersed through the sonication method followed by calendering process to ensure an optimum enhancement in the properties of polymer matrix can be achieved. The results show positive improvement in terms of strength and Young’s modulus of tested grout with the inclusion of GnPs. It shows that the presence of low concentration of GnPs as an additive has a significant reinforcement effect by improving tensile properties of epoxy grout up to 14% as compared to control sample.